Eksperimen Pembelajaran Matematika Dengan Strategi Problem Based Learning Dan Numbered Head Together Terhadap Hasil Belajar Ditinjau Dari Motivasi Belajar Siswa Kelas VIIIMTs Negeri 1 Surakarta - Ningsih, Cahyo; , Drs. Slamet HW, M. M., M. Pd (2017)
ABSTRACT The purpose of the research are to analyze: (1) the effect of learning strategiesProblem Based Learning and Numbered Head Together on learning outcome; (2) the effect of student's motivation to learning outcome;(3) the interaction between learning strategy and learning motivationonlearning outcomes. Type of research quantitative with quasi-experimental design.Sample were taken by Cluster random sampling of the population of the research was all students of class VIII MTs Negeri 1 Surakarta in academic year 2016/2017. Data collection technique byusing questionnaire, test and documentation. Before to the analysis, first tested the normality and homogeneity test. The hypothesis test use unbalance two way analysis of variance with α= 5%. The results of this study showsed: (1) there was the effect of learning strategies Problem Based Learning and Numbered Head Together on learning outcome; (2) there was not effect of student's motivation to learning outcome; (3) there was not interaction between learning strategy and learning motivation on learning outcomes. Keyword: Problem Based Learning, learning outcome, Numbered Head Together, learning motivation